Regeneration Through in vivo Cell Fate Reprogramming for Neural Repair - Tai, Wenjiao; Xu, Xiao-Ming; Zhang, Chun-Li (Frontiers in Cellular Neuroscience, 2020)
The adult mammalian central nervous system (CNS) has very limited regenerative capacity upon neural injuries or under degenerative conditions. In recently years, however, significant progress has been made on in vivo cell fate reprogramming for neural regeneration. Resident glial cells can be reprogrammed into neuronal progenitors and mature neurons in the CNS of adult mammals. In this review, we briefly summarize the current knowledge on innate neurogenesis under pathological conditions and then focus on induced neurogenesis through cell fate reprogramming. We discuss how the reprogramming process can be regulated and raise critical issues requiring careful considerations to move the field forward. With emerging evidence, we envision that fate reprogramming-based regenerative medicine will have a great potential for treating neurological conditions such as brain injury, spinal cord injury, Alzheimer’s disease, Parkinson’s disease, and retinopathy.